Diagnostic and therapeutic outcomes of pediatric colonoscopies in Jordanian children - Eyad Altamimi; Yousef Odeh; Tuka Al-quraan; Elmi Mohamed; Naif Rawabdeh (Hygeia Press di Corridori Marinella, 2022)
Background: Pediatric colonoscopy is a crucial tool for diagnosing and treating children with colonic diseases. Data from low-volume centers are scarce and, most of the time, not represented in literature. This study aimed to review colonoscopy indications, diagnostic yield, therapeutic interventions, and outcomes in children who underwent a colonoscopy procedure at a university hospital in North Jordan.  Methods: A retrospective review was conducted on children who underwent colonoscopies between January 2014 and January 2020. Demographic data, procedure indications, and colonoscopy and histopathological findings were collected from patient hospital charts. The appropriateness of colonoscopy indications was judged according to published guidelines.  Results: We identified 119 procedures performed in 105 children (females: 39 [37.1%]; mean age: 98.2 ± 51.2 months) in our review. The most common cause for undergoing a colonoscopy procedure was lower gastrointestinal bleeding (55 [46.2%]), followed by chronic diarrhea and abdominal pain (17 [14.3%] and 16 [13.4%], respectively). A normal endoscopy was reported in 50 (42.0%) procedures. The most commonly reported abnormalities were polyps and inflammatory bowel disease. Polypectomies were performed in 21 patients during 26 (21.8%) procedures. Most of the polyps were rectal polyps (15 [71.4%]), and all of them were of juvenile pathology. Appropriate colonoscopy indications were associated with a higher rate of an abnormal endoscopy.  Conclusion: Low-volume centers share a similar spectrum of disorders reported by larger centers. Our study found that the most common colonoscopy indications were rectal bleeding and diarrhea, and the most common findings were colonic inflammation and colorectal polyps. Complying with guideline recommendations will improve the diagnostic yield of colonoscopies.